(untitled) (International Journal of Engineering and Computer Science, 2013)
The dependence of numerous systems on electronic devices is causing rapidly increasing concern over fault tolerance. At the system level. Redundancy is a technique that has been used to improve space electronic systems reliability. The traditional implementation has been to incorporate redundancy by having the passive or active availability of two separate boxes that perform the same function. This paper argues that redundancy in engineering, should be understood as a ‘design paradigm’ that frames regulatory assessments and interpretations of all complex technical systems, profoundly shaping decisions and judgments about modern technologies. The purpose of this paper is to provide a brief overview of redundancy